Treatment of Alveolar Bone Necrosis and Gingival Recession Following Removal of Gutta-Percha by Fiber Post Drills: A Case Report - Altaş, Nurcan (Hasanuddin University, 2021)
Objective: The purpose of this article is to report the clinical manifestations and management of bone and gingival damage caused by fiber post drills.Methods: A 43-year-old patient reported that she had pain for 3 weeks that began after post placement. Once the pain had subsided, she noticed gingival recession on the mandibular left canine. A review of her history revealed that post drills were used without water cooling. In the clinical examination, bone exposure and attachment loss were observed. During periodontal plastic surgery, the necrotic bone was removed, and a free gingival graft was placed in the area.Results: After 10 days sutures were removed and 8 months later gingival healing was quite good.Conclusion: This case report shows periodontium may be damaged when fiber post drills are used to remove gutta-percha. Therefore, it is recommended that clinicians use instruments according to the manufacturer’s instructions and refer patients to a specialist when complications occur.